ENERGY-BASED PHARMACOPHORE MODELING, VIRTUAL SCREENING, AND MOLECULAR DYNAMICS TO IDENTIFY POTENTIAL INHIBITORS FOR GLYCOGEN SYNTHASE KINASE 3 BETA - Jb, Sheema; Hopper, Waheeta (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Â Objective: Glycogen synthase kinase 3 beta (GSK3Î²) is one of the main targets for wound healing activity. Our objective is to identify novel inhibitors for GSK3Î² using in silico approach. Methods: Grid-based molecular docking, energy-based pharmacophore (e-pharmacophore) modeling, and molecular dynamics (MD) studies were performed for phytocompounds with GSK3Î² and compared with standard drugs using Schrodinger software. Results: The glide scores and the molecular interactions of the phytocompounds were well comparable to the standard drugs. The MD was performed for the target bound to the best scoring ligand, entagenic acid. The pharmacophore features of this docked complex were modeled as e-pharmacophore. The constructed e-pharmacophore model was screened against phytocompounds retrieved from literature to identify the ligands with similar pharmacophore features. Conclusion: The glide scores of fukinolic acid, cimicifugic acid, and linarin were âˆ’10.99, âˆ’8.28, and âˆ’7.25 kcal/mol, respectively. The further 50 nanoseconds MD study determined the stability of GSK3Î²-linarin complex. Nitrofurazone and sulfathiazole drugs can lead to systemic side effects. Hence, it is concluded that linarin could be a potent wound healing compound against GSK3Î².